Exercises in activating lymphatic system on fluid overload symptoms, abnormal weight gains, and physical functions among patients with heart failure: A randomized controlled trial - Li, Yuan; Meng, Qingtong; Luo, Biru; Li, Minlu; Fang, Jinbo; Allred, Sarah R.; Fu, Mei Rosemary (Frontiers in Cardiovascular Medicine, 2023)
Background: Fluid overload remains a vexing problem in management of heart failure. The lymphatic system that plays the central role in fluid homeostasis has recently been explored as a potential target to counteract tissue fluid overload. The goal of the study was to evaluate the preliminary effects of exercises in activating lymphatic system on fluid overload symptoms, abnormal weight gains, and physical functions for patients with heart failure. Methods and results: A pilot, pre- and post-test, randomized clinical trial was conducted to recruit a total of 66 patients who were randomized to receive either a 4-week The-Optimal-Lymph-Flow for Heart Failure (TOLF-HF) program or usual care alone. The primary outcome was the prevalence and burden of the fluid overload symptoms. Findings of the trial showed that the TOLF-HF intervention was effective in reducing the prevalence or burden of the majority of fluid overload symptoms. TOLF-HF intervention also demonstrated significant improvement in the outcomes of abnormal weight gains (MD -0.82; 95% CI -1.43 to -0.21; P = 0.010) and physical functions (F = 13.792, P < 0.001). Conclusions: The TOLF-HF program focusing on activating lymphatic system through the performance of therapeutic lymphatic exercises holds the promise as an adjuvant therapy for patients with heart failure to manage fluid overload symptoms, reduce abnormal weight gains, and improve physical functions. Future larger-scale study with longer duration of follow-up is needed.